2016
DOI: 10.1021/acs.langmuir.6b01995
|View full text |Cite
|
Sign up to set email alerts
|

Stealth Amphiphiles: Self-Assembly of Polyhedral Boron Clusters

Abstract: This is the first experimental evidence that both self-assembly and surface activity are common features of all water-soluble boron cluster compounds. The solution behavior of anionic polyhedral boranes (sodium decaborate, sodium dodecaborate, and sodium mercaptododecaborate), carboranes (potassium 1-carba-dodecaborate), and metallacarboranes {sodium [cobalt bis(1,2-dicarbollide)]} was extensively studied, and it is evident that all the anionic boron clusters form multimolecular aggregates in water. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…We further concluded that the chaotropic effect presents a generic driving force that accounts for the intrinsic affinity of chaotropic ions, prominently anions, for neutral organic or inorganic matter, including concave macrocyclic binding sites, lipid bilayers, membranes, and polymers 11, 12, 13, 16, 17, 18, 22, 24, 28, 40, 43, 44, 45, 46, 47, 48. It should be noted that indications for the affinity of anions to hydrophobic binding sites existed early in the literature81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103 but were in part attributed to a putative hydrophobic (or lipophilic) property of large anions, implying the hydrophobic effect as driving force.…”
Section: Thermochemical Hydration Characteristicsmentioning
confidence: 84%
See 3 more Smart Citations
“…We further concluded that the chaotropic effect presents a generic driving force that accounts for the intrinsic affinity of chaotropic ions, prominently anions, for neutral organic or inorganic matter, including concave macrocyclic binding sites, lipid bilayers, membranes, and polymers 11, 12, 13, 16, 17, 18, 22, 24, 28, 40, 43, 44, 45, 46, 47, 48. It should be noted that indications for the affinity of anions to hydrophobic binding sites existed early in the literature81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103 but were in part attributed to a putative hydrophobic (or lipophilic) property of large anions, implying the hydrophobic effect as driving force.…”
Section: Thermochemical Hydration Characteristicsmentioning
confidence: 84%
“…The tendency of different boron clusters (B 10 H 10 2− , B 12 H 12 2− , B 12 H 11 SH 2− , 1‐carbadodecaborate, and cobalt bis(1,2‐dicarbollide)) to self‐assemble into aggregates and colloids in water has been detailed by Matějíček and co‐workers,11, 188, 190, 193 while the group of Bauduin and Diat have described the formation of charged nano‐colloids from POMs 15. The unusual behavior of anionic boron clusters can again be attributed to the chaotropic effect, which complements the classical hydrophobic effect as a supramolecular assembly and self‐assembly motif in water (Figure 10).…”
Section: Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Isothermal titration calorimetry (ITC) was used to determine the absolute binding constants and to analyze the complexation thermochemistry (Figure ); access to this technique was essential, because the binding turned out to be too strong to employ NMR titrations for accurate determination of the binding constants ( K a ). An ITC dilution titration of B21 (1 mM) was performed first; no significant heat effect was observed, which excluded a competitive enthalpic effect due to micellization/de‐aggregation events (reported for ortho ‐COSANs), and the subsequent host‐guest titrations were performed at much lower B21 concentrations (0.1 mM). The ITC titration profiles were consistent with a 1 : 1 binding stoichiometry, consistent with the mass‐spectrometric study, in which also no 2 : 1 host‐guest complexes had been observed .…”
Section: Figurementioning
confidence: 99%